TI_GERICHTE 12.2008.148 vom 2. Februar 2010 , Appalto - ammontare della mercede - norma SIA 118 - onere della prova - TI Tribunale d'appello (2010)
Appalto - ammontare della mercede - norma SIA 118 - onere della prova